Pathological processes and conservation state of the religious heritage along the Adobe Route (Catamarca, Argentina) - Herr, Carola I.; Rolón, Carlos Guillermo (Estoa. Journal of the Faculty of Architecture and Urbanism, 2026)
The Adobe Route, in Tinogasta (Catamarca, Argentina), constitutes a cultural itinerary whose religious heritage is mostly built with adobe. This initial study is part of a broader project aimed at developing a heritage management plan and seeks to answer: what are the main damage and agents of deterioration, decay and alteration in these buildings? 11 cases, promoted by the provincial Secretariat of Tourism, were surveyed using records based on the ICOMOS-ISCEAH glossary, documenting qualitatively and quantitatively the families of damages and agents of deterioration, decay and alteration. Results show the prevalence of processes related to material loss, cracks, deformations, and detachments, mainly caused by anthropic and atmospheric agents. A conservation state ranging from good to fair was observed, with low to medium intervention priorities. The discussion highlights the tension between vernacular techniques and industrialized materials. It is concluded that preservation requires differentiated strategies that integrate technical, community, and cultural criteria.